The Metaphor “Knowledge Rooted in the Heart”: A Pragmatic Analysis in Moral Education Discourse - Isnaeni, Isnaeni (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study explores the use of the metaphor “knowledge rooted in the heart” in a speech delivered by the Minister of Primary and Secondary Education, Abdul Mu'ti, at Pondok Pesantren Amanatul Ummah. Employing a pragmatic approach, the article examines how the metaphor functions within its communicative setting, what is being emphasized, how the message is oriented toward the audience, and which values are legitimized through specific linguistic choices. The phrase “knowledge in the heart” is interpreted not merely as a poetic expression, but as an insistence on the internalization of values in the educational process. From a pragmatic standpoint, the utterance carries normative force, inviting, advising, and reaffirming that knowledge should not remain confined to cognitive achievement but should develop into character. In another part of the speech, references to technology and artificial intelligence articulate a critical position, namely that technology should be mastered while human beings must remain in control rather than becoming dependent on it. The formulation of three qualities, knowledgeable, capable, and humble, signals an effort to integrate intellectual competence, practical skills, and moral integrity within a unified educational framework. The findings suggest that metaphor operates as a rhetorical device that strengthens moral messages, fosters emotional engagement with the audience, and underscores an educational orientation centered on cultivating knowledgeable and virtuous individuals. Therefore, the discourse functions not only informatively but also persuasively and ideologically in shaping a vision of future generations.